Advances in proton therapy technology and global clinical applications - Zhang, Qi; Yang, Wencui; Tan, Lina; Guo, Xiangyu; Wang, Tao; Zhu, Pengfei; Jing, Zhouchen; Ma, Lei; Hou, Jun (Frontiers in Oncology, 2026)
Proton therapy, by leveraging its unique physical characteristic of the Bragg peak, enables high-precision dose delivery to the tumor target while effectively protecting surrounding normal tissues, and has become an important representative of advanced radiotherapy. This review aims to systematically summarize key technological breakthroughs in recent years that have driven the progress of proton therapy, including compact superconducting accelerators, pencil beam scanning (PBS), image-guided proton therapy (IGPT), and the transformative ultra-high dose rate FLASH radiotherapy, while highlighting the role of artificial intelligence (AI) in advancing proton therapy toward real-time adaptive precision radiotherapy. The article also explores the global distribution and development status of proton centers, with a specific analysis of China’s notable advancements as an emerging market in center construction, equipment localization, and the treatment of characteristic local tumor types. Moving forward, it is essential to continue promoting technological integration and innovation, strengthen high-quality clinical research, and develop a more accessible, intelligent, and personalized proton therapy system to achieve broader clinical application and patient benefit.